Landlords and property social relations in the private rented sector - Allen, John 1951- (Cambridge human geography, 1989)
The issue of private landlordism in Britain touches a raw political nerve. There is no shortage of prescription as to what should be done with the rented housing market and private landlords. Yet surprisingly little is known about the structure and diversity of private landlordism and the variety of private tenants' housing needs - a prerequisite for policy intervention. This book provides an anatomy of the nature of private landlordism in the 1980s, the types of landlord in the market, the scope of their activities, and the choices and constraints that guide their actions in the market. It shows how the pattern of change in the private rented sector has been not one of straightforward decline, but one of structural unevenness shaped by a combination of three general processes - disinvestment, investment and informalization - which vary in impact from place to place. Adopting a realist methodological approach, the authors attempt to capture both the general characterisation of landlordism and the processes shaping the private rental sector and their diverse geographical form across space and through time. This approach is illustrated by an extensive investigation in two local housing markets in inner London. Finally, the authors examine the scope for change in the private rented sector and argue for a combination of public and private initiatives that is sensitive to the differences among local housing markets and that relates to the demands/needs of those groups at present dependent on private renting for accommodation